Dinamika Pendidikan Pesantren di Muhammadiyah - Kuswandi, Iwan (SHAHIH: Journal of Islamicate Multidisciplinary, 2020)
This paper examined the dynamics of pesantren education within Muhammadiyah. This study used a conceptual research approach. There are three main topics being discussed in this paper, namely the context of use, periodization and continuity. The study found that Muhammadiyah and pesantren seems to be two contradictory poles. While Muhammadiyah is known for its modernity, pesantren is known as a traditional religion institution. However, both Muhammadiyah and pesantren can be united in one obsession. It was started by Kiai Dahlans criticism about pesantren system, which then criticized back by Kiai Fachriuddin who later adopted pesantren system for use in the organization. The dynamics of pesantren in Muhammadiyah were found in the wide range variety of pesantren models its developed, namely integral system, takhassus, boarding school systems, and modern pesantren.